EVALUATING THE EFFECTIVENESS OF MURABAHAH FINANCING IN PROMOTING MSME DEVELOPMENT - Muhammad Aulia Rohman; Annikmah Farida; Nur Alfi Khotamin (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This research is motivated by the importance of Islamic financing in supporting the growth of micro, small, and medium enterprises (MSMEs), particularly through the Murabahah contract, which is the flagship product at BMT Asy-Syafi’iyah Kota Gajah. Murabahah financing is considered capable of providing affordable, transparent, and Sharia-compliant capital solutions, thus requiring an evaluation of its implementation effectiveness for MSME actors. This study aims to determine the extent to which Murabahah financing contributes to business development, ease of access to financing, and the suitability of fund usage with business needs. The research method used is a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation, with informants consisting of the head of BMT, account officers, and Murabahah financing customers. Data analysis was conducted through reduction, presentation, and conclusion drawing, with triangulation as the validation technique. The results show that Murabahah financing at BMT Asy-Syafi’iyah Kota Gajah effectively increases business turnover, expands production capacity, and facilitates working capital for MSME actors. Easy application procedures, direct mentoring, and the alignment of funds with business needs are the main supporting factors for the effectiveness of this financing. Thus, Murabahah financing is proven to play a positive role in empowering MSMEs sustainably